2016
DOI: 10.1371/journal.pone.0162073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Exposure to an Electronic Containment System on the Behaviour and Welfare of Domestic Cats

Abstract: Free-roaming cats are exposed to a variety of risks, including involvement in road traffic accidents. One way of mitigating these risks is to contain cats, for example using an electronic boundary fence system that delivers an electric ‘correction’ via a collar if a cat ignores a warning cue and attempts to cross the boundary. However, concerns have been expressed over the welfare impact of such systems. Our aim was to determine if long-term exposure to an electronic containment system was associated with redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 73 publications
1
8
0
1
Order By: Relevance
“…The physical barrier systems studied here appear to be highly effective in providing a controlled environment to the outside for cats without the risk inherent within some other systems e.g., electronic boundary systems ( 44 ). These systems appear to provide significant improvements to various aspects of cat welfare.…”
Section: Discussionmentioning
confidence: 99%
“…The physical barrier systems studied here appear to be highly effective in providing a controlled environment to the outside for cats without the risk inherent within some other systems e.g., electronic boundary systems ( 44 ). These systems appear to provide significant improvements to various aspects of cat welfare.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral prioritization, by integrating several critical considerations and viewpoints, and not exclusively the conservation benefit, also exposed and quantified particular values and beliefs that could significantly impact the success of a campaign. For example, 67% of veterinarians thought that keeping cats inside 24 hr a day would have a significant negative impact on cat welfare (a belief that might not be always true, for example, Kasbaoui et al, ), although it would also reduce cats' hunting to zero. Moreover, 24‐hr containment is a behavior that cat owners identify as unlikely to be achievable.…”
Section: Prioritising Behaviors For a Campaignmentioning
confidence: 99%
“…Kasbaoui and colleagues [8] found that on average, outdoor owned cats in England travelled 4.4 kilometers a day, suggesting cats spend a significant portion of their day travelling and exploring. Exploration allows cats to experience variety in a range of different environments, and also provides physical exercise, which can be good for cat health.…”
Section: Natural Behaviorsmentioning
confidence: 99%
“…Although there are many potential welfare risks associated with uncontrolled outdoor access for cats, it has also been suggested that access to the outdoors has various benefits to cat welfare [7]. For example, it has been suggested that outdoor environments have increased natural enrichment and space for exploration, which provides for greater mental stimulation [8], and conversely, that keeping cats indoors prevents them from performing natural behaviors, such as exploring, climbing, and hunting, which might lead to boredom, frustration and increased behavioral problems [9]. Some also argue that outdoor access can improve cat health through increased physical activity [10], as they have more opportunities to roam, jump, and run.…”
Section: Introductionmentioning
confidence: 99%